An Experimentally Validated Cavitation Model for Hydrodynamic Bearings Using Non-Condensable Gas - Sören Wettmarshausen; Alexander Engels; Thomas Hagemann; Michael Stottrop; Christoph Weißbacher; Hubert Schwarze; Beate Bender (Lubricants)
Despite great research effort in recent decades, cavitation in hydrodynamic journal bearings is still a not completely understood phenomenon. In particular, it is unclear which proportions of different cavitation types are present in a bearing. Novel experimental results show a clear deviation from the predictions of hydrodynamic lubrication theory. This article presents a new approach for modeling cavitation in hydrodynamic bearings by using computational fluid dynamics with the volume of fluid method and a phase of non-condensable gas in the lubrication oil. The validation of the model is achieved through the simulation of a large Offset-Halves Bearing and a subsequent comparison of the results with various experimental data, including the fractional film content. In the results, cavitation also occurs in the convergent gap due to a pressure drop caused by inertia forces. The findings indicate that the cavitation effects in oil-lubricated hydrodynamic bearings are caused by a special form of gaseous cavitation, designated as pseudo-cavitation. The presented model with non-condensable gas is able to reproduce the observed phenomena excellently.